2018
DOI: 10.1007/s00417-018-3994-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of the vitreous body in effective IOL positioning

Abstract: An adjusted ELP parameter to optimize IOL calculation may be useful in eyes undergoing combined phacovitrectomy sugergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
1
12
0
1
Order By: Relevance
“…Overall, our results are compatible with those of previously reported studies, with a slight myopic error of approximately −0.5 D. 4 , 7 , 8 A recent meta-analysis comparing combined phacovitrectomy and sequential surgery concluded that there were no significant differences in visual and refractive outcomes between the two. 13 However, some studies have reported that combined phacovitrectomy is associated with lower refractive accuracy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, our results are compatible with those of previously reported studies, with a slight myopic error of approximately −0.5 D. 4 , 7 , 8 A recent meta-analysis comparing combined phacovitrectomy and sequential surgery concluded that there were no significant differences in visual and refractive outcomes between the two. 13 However, some studies have reported that combined phacovitrectomy is associated with lower refractive accuracy.…”
Section: Discussionsupporting
confidence: 92%
“…The addition of vitrectomy was associated with an induced myopia of approximately −0.4 to −0.5 diopter. 4 , 7 , 8 The addition of gas at the end of surgery did not cause a significant change, and the PE was lower in patients that underwent vitrectomy for macular holes (MH). 8 PE was also associated with shallower anterior chamber depth (ACD) at presentation, increased central macular thickness (>300μ), and worse baseline best-corrected visual acuity.…”
Section: Introductionmentioning
confidence: 99%
“… Regarding the post-operative axial length (AL) we do not agree that an increased AL is necessarily expected. Vander Mijnsbrugge et al 2 measured postoperative AL and also did not find a significant difference. We agree that the non-significant difference between groups could be explained by limited number of examined patients, and have noted this point as a limitation of our study.…”
Section: Dear Editormentioning
confidence: 94%
“… 1 The slightly lower accuracy of the predicted refraction after combined phaco-vitrectomy with a small myopic shift was also shown in previous studies. 2 , 3 The scope of this study was to look at the ACD after surgery as a post-surgery measurement of the effective lens position (ELP). We wanted to find whether it correlates with the post-surgical error in the targeted refraction or the use of gas during the surgery.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation